Weekday dependence of German stock market returns - Helmut Herwartz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
The so-called 'Monday effect ' has been found for various stock markets of the world. The empirical finding that Monday returns are significantly smaller than returns measured for the remaining days of the week calls the efficiency hypothesis for pricing processes operating on stock markets into question. Investigating an index series measured at the Frankfurt stock exchange the paper compares estimation results of parametric and nonparametric autoregressive models with respect to possible weekday dependence of return data. Allowing for heteroskedastic error distributions the wild bootstrap is used to infer against time varying means and correlation of return data in parametric models and to obtain confidence bands for nonparametric estimates. It is shown that time dependence is an important feature describing the dynamics of German stock market returns in the period 1960-79. Within two subsamples obtained from the period 1980-97 the evidence in favour of such effects is mitigated substantially.
urn:nbn:de:kobv:11-10046385
Keywords: C14; C22; G14; 330; Periodic models; weekday effects; wild bootstrap; nonparametric autoregression